Between-day reliability of the Hamstring Solo device during the Nordic Hamstring curl. - Darrall-Jones, J.; Breen, D.; Roe, G.; Till, K.; Jones, B. (Journal of Australian Strength and Conditioning, 2021)
The purpose of this study was to determine the between-day reliability of the Hamstring Solo for measuring peak eccentric knee flexor force (EKF) during the Nordic hamstring curl. Data were collected on 18 male Professional rugby union players across two testing sessions separated by 7 days. There was no between-session difference in EKF force for left (p = 0.440 - 0.580) or right (p = 0.477 - 0.656) leg when using the best of 1 (left = 405.3±88.2 N vs. 412.8±92.7 N; right = 408.0±88.1 N vs. 416.7±85.2 N), 2 (left = 409.9±87.6 N vs. 415.0±96.2 N; right = 413.0±87.5 N vs. 418.3±86.2 N), or 3 repetitions (left = 411.2±88.2 N vs. 417.3±92.7 N; right = 417.7±87.4 N vs. 417.7±87.4 N). The between-day reliability of EKF peak force was acceptable for left (7.2 to 8.3%) and right (8.3 to 9.8%) leg, with the typical error lowest when using the best of three repetitions. The smallest worthwhile change (SWC) was similar for left (4.2 - 4.3%) and right (3.6 - 3.7%) when using the best of 3 repetitions. As the typical error was greater than the SWC for both the left (1.71 x the SWC) and right (2.24 x the SWC) legs, changes of 2.71 (Delta 41 N; 11%) and 3.24 (Delta 47 N; 12%) xSWC are required to detect a small change in EKF peak force, taking into account the typical error. Practitioners can use the reliability statistics from this study to monitor EKF peak force in professional rugby union players, when using the Hamstring Solo device. It is recommended that when monitoring EKF peak force with the Hamstring Solo, practitioners use the best of 3 repetitions.